Macrophomina phaseolina: General Characteristics of Pathogenicity and Methods of Control - Marquez, Nathalie; Giachero, María L.; Declerck, Stéphane; Ducasse, Daniel A. (Frontiers in Plant Science, 2021)
Macrophomina phaseolina is a generalist soil-borne fungus present all over the world. It cause diseases such as stem and root rot, charcoal rot and seedling blight. Under high temperatures and low soil moisture, this fungus can cause substantial yield losses in crops such as soybean, sorghum and groundnut. The wide host range and high persistence of M. phaseolina in soil as microsclerotia make disease control challenging. Therefore, understanding the basis of the pathogenicity mechanisms as well as its interactions with host plants is crucial for controlling the pathogen. In this work, we aim to describe the general characteristics and pathogenicity mechanisms of M. phaseolina, as well as the hosts defense response.We also review the current methods and most promising forecoming ones to reach a responsible control of the pathogen, with minimal impacts to the environment and natural resources.